HUBUNGAN ANTARA PEMBERIAN ASI EKSKLUSIF DENGAN KEJADIAN ISPA PADA BALITA USIA 7-24 BULAN DI POSKESDES LEMPER WILAYAH KERJA PUSKESMAS PADEWAWU - yulia paramita rusady; layla imroatu zulaikha (Universitas Banten Jaya, 2022)
Infancy and toddler years are the best period to receive nutritional intake. The better the nutritional intake, the better the physical development and immunity. At the age of the two yeard old baby, the infection rate is high because the antibodies formed have not been maximized. Infections that often attack toddlers at that age include diarrhea, fever and upper respiratory tract infection. Data obtained from Lemper Village shows that the diseases that attack children under five in January 2021 are 50% upper respiratory tract infection, 33% diarrhea and 16% fever. These data indicate that upper respiratory tract infectionis a disease with the highest percentage that attacks toddlers. From the results of the preliminary study, it was found that 10 mothers with upper respiratory tract infection under five, 5 children were not given exclusive breastfeeding, 3 people had low body weight, and 2 people lived in a smoking family environment. Based on the research objectives, the research design used was an analytical survey with a cross sectional research design. Based on the results of the study showed that almost entirely (80.0%) of mothers who gave exclusive breastfeeding did not experience upper respiratory tract infection as many as 16 mothers, while infants who were not exclusively breastfed (81.9%) had ARI as many as 36 toddlers. The results of the statistical test show that the calculated X2 value = 22.42 is greater than the table X2 value = 3.841. It can be concluded that Ho is rejected while H1 is accepted, meaning that there is a relationship between exclusive breastfeeding and the incidence of upper respiratory tract infection in children aged 7–24 years in Lemper Village. The importance of the benefits of exclusive breastfeeding for infants can reduce the number of infections in infants, thus enabling mothers to improve their lifestyle. Because exclusive breastfeeding contains a lot of antibodies, so that babies who are breastfed have antibodies that increase so that it will reduce the incidence of upper respiratory tract infection. The conclusion in this study is that there is a relationship between exclusive breastfeeding and the incidence of upper respiratory tract infection in toddlers aged 7-24 months at the Lemper Village Health Care. Mothers of toddlers are advised to be more active in participating in any counseling on breastfeeding techniques to prevent the occurrence of upper respiratory tract infection in infants. Keywords: Exclusive breastfeeding, upper respiratory tract infection, baby